THE EFFECT OF PROBLEM BASED LEARNING AND INQUIRY LEARNING LEARNING MODELS ON ECOSYSTEM CONCEP TO IMPROVE CRITICAL THINKING, AND CREATIVE THINKING, ABILITY OF STUDENTS SMA NEGERI 11 AMBON, SMA NEGERI 13 AMBON AND MADRASAH ALIYAH NEGERI AMBON. - Serang, Nur Fatahila; Pattipeilohy, Mery; Rehena, Johanis Fritzgal (Universitas Pattimura, 2021)
Many abilities that students must have, namely the ability to think critically, think creatively, construct knowledge, solve problems and master learning material well. One of the efforts to improve students' critical thinking and creative thinking skills is to change the old learning model used with the problem-based learning model and inquiry learning model. Students think more critically and think creatively and encourage students to be able to connect between the knowledge they have and its application in their daily lives. This study aims to determine the effect of two learning models, namely problem-based learning and inquiry learning to improve critical thinking skills and creative thinking on ecosystem material in class X SMAN 11, SMAN 13, and Madrasah Aliyah. The type of research is Quasi Experiment using 3 experimental classes using the problem based learning model and 3 experimental classes using the inquiry learning model. The statistical analysis used was multiple linear regression using SPSS 22. The results obtained from multiple linear regression analysis both had significant values <0.05 using both problem based learning and inquiry learning models at SMA N 11, SMA N 13 and Madrasah Aliyah Negeri Ambon. Conclusion. There is an influence of the use of problem-based learning models and inquiry learning models to improve the ability to think in class X SMAN 11, SMAN 13 and Ambon Madrasah Aliyah.